Inhibitory Effects of Resveratrol against Mitochondrial Toxicity Induced by Perfluorooctanoic Acid in Isolated Liver Mitochondria of Male Rats - Maloos Naderi; Mozhdeh Seifi; Sholeh Akbari; Fatemeh Shaki (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Resveratrol (RSV) is a naturally polyphenolic compound found in grapes and other plant sources. It has potent free radical scavenger and antioxidative properties.The aim of this study was to evaluate the protective effect of resveratrol against Perfluorooctanoic acid (PFOA) induced mitochondrial toxicity in isolated liver mitochondria. Materials and methods: Mitochondria were isolated from fresh male rat’s liver tissues using differential centrifugation technique. Then, the isolated mitochondria were divided into the following groups: control, PFOA (1mM), PFOA plus RSV (50, 100, and 200 µM), and PFOA plus Vit C (positive control). The effects of PFOA were assessed on a series of mitochondrial parameters including mitochondrial function, reactive oxygen species (ROS) formation, lipid peroxidation (LPO), protein carbonyl, and glutathione (GSH) content. Data were analyzed using GraphPad Prism version 6. Results: PFOA induced mitochondrial dysfunction in isolated liver mitochondria. Resveratrol markedly alleviated mitochondrial dysfunction-induced by PFOA in isolated liver mitochondria. Conclusion: Resveratrol showed protective effect against PFOA induced hepatotoxicity which may be attributed to its antioxidant activity. So, it can be considered as an effective supplement against oxidative stress and mitochondrial dysfunction induced by PFOA exposure in isolated liver mitochondria.